A Reliable Routing Protocol for Vehicular Ad hoc Networks. (November 2017) - Saleh, Ahmed I.; Gamel, Samah A.; Abo-Al-Ez, Khaled M.
Abstract: This paper introduces a Reliable Routing Protocol (R 2 P) for Vehicular Ad-hoc Networks (VANETs), which divides the network into overlapping zones. For each zone, a special node is promoted to be the Master Node (MN), which maintains an up-to-date routing boards for inter/intra-zone communication. R 2 P depends on two types of boards, namely; Internal Routing Board (IRB) and External Routing Board (ERB). Two types of IRB are used, namely; Zone Routing Board (ZRB) that is maintained by MNs, and Private Routing Board (PRB) that is maintained by each network node. Both ZRB and PRB register routes among zone nodes, while ERB, which is maintained by MN, registers available gateways to neighboring zones. R 2 P employs a special route discovery mechanism to discover available routes to the destination, and then elects the most reliable route. It has been compared against the recent VANET's routing protocols. Experimental results have shown that R 2 P outperforms the others.